Analisis pengendalian kualitas produk roti menggunakan metode taguchi pada UMKM Roti Masempo - Safitri, Rindiani; Wolok, Eduart; Lahay, Idham Halid (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study was conducted to improve the quality of bread products at UMKM Roti Masempo using the Taguchi method. The aim of the research was to investigate the main causes of defects in bread products and determine the optimal combination of process parameters to reduce defect rates. The Taguchi method was applied with the "smaller-the-better" characteristic to analyze factors contributing to product defects. The experimental design utilized an L9(3²) orthogonal array to simplify the combinations of factors tested. The study's findings indicated that the optimal combination to reduce bread product defects involved a baking temperature of 170°C for the top and 175°C for the bottom (level 2), along with a baking time of 18 minutes (level 1). With this setting, the risk of defective products decreased from an initial range of 15–30 defective breads to 3.24–5.25 defects at UMKM Roti Masempo.